(untitled) (Journal of the College of Education for Women, 2024)
This study explores the connection between environmental degradation and gender oppression through an ecofeminist perspective, focusing on Lynn Nottage’s Ruined. It examines how capitalist and patriarchal systems exploit both women and nature, particularly in the civil war-torn Democratic Republic of the Congo. Drawing on materialist ecofeminism as defined by Mary Mellor, the study demonstrates how gender-based power dynamics reflect the extraction and commodification of natural resources for profit. Nottage’s Ruined highlights the intertwining crises of environmental and gender injustices, with its portrayal of violence against women serving as a metaphor for broader ecological devastation driven by capitalist interests. The paper argues that addressing ecological crises requires confronting the systemic power structures that perpetuate both gender-based violence and environmental degradation.